Kinetics of the Adsorption of Chromium(VI) Ions from Water by Vegetable Precursors Treated with Sulphuric Acid - Seyf-Laye Alfa-Sika Mande; Mingzhu Liu; Fei Liu; Honghan Chen (Adsorption Science & Technology)
The removal of chromium(VI) ions from water and wastewater through the use of activated maize cob (AMC) and activated banana peel (ABP) has been studied. In addition, the kinetics of the adsorption of Cr(VI) ions onto AMC and ABP were investigated. The effects of altering the initial Cr(VI) ion concentration, contact time and temperature on the removal process were studied. The removal of Cr(VI) ions increased with increasing temperature and depended on the initial Cr(VI) ion concentration, with complete removal being effected after a contact time of 80 min and 600 min for AMC and ABP, respectively. The process of Cr(VI) ion removal followed pseudo-second-order kinetics with the rate constants being determined at different temperatures in the range 20–40 °C. The activation energies for the adsorption of Cr(VI) ions onto AMC and ABP were calculated as 56.74 kJ/mol and 86.47 kJ/mol, respectively. Thermodynamic parameters such as the standard Gibbs' free energy change (Δ ads G 0 ), the standard entropy change (Δ ads S 0 ) and the standard enthalpy change (Δ ads H 0 ) were calculated. The thermodynamic studies revealed that the values of Δ ads H 0 were positive, suggesting that the adsorption process was endothermic in nature.